Analyzing The Content of Senior High School Textbooks Towards SLA-Based Principles - JMMatai PSDKU; Vonny Juliana Ruhulessin (MATAI: International Journal of Language Education, 2021)
This research outlined framework for English textbooks analysis from the perspective of Second Language Acquisition (SLA). The aims are to find out the parts of the material which are in line with SLA principles and the part of the material which are not in line with SLA principles. These parts of the textbooks were analyzed using modified version of Littlejohn’s (materials development in language teaching, 2011) analysis task. The English textbooks were analyzed entitled Pathway to English for Senior high School, published by Erlangga, for Grade X ; XI and XII. The data were assessed by sign, plus point when the features in modified Littlejohn analyzing task are in line with SLA and minus pointwhen they are not. In the data analysis technique, the percentage of initiate shows 99% activity/task initiating learner to respond the instruction which is in line with SLA principles, whilst only 1% is not required respond which are not in line with SLA principles. The part of focus shows plenty activity promoting meaningful task with 51% whilst focus on form with 12%. The part shows that they are in line with SLA principle for giving more focus on meaning. In part of mental operation, the percentage shows most activities covered the features of SLA principles, only 1 % pointed to task which is not line with SLA principles (repeat/reproduce with substitution). In part of who with, individual work dominated the tasks with 60%, individual/pair/group/whole class with 24%, whilst presentation both in group/pair with 2%. In the part of content, the percentage shows most input materials to learners are written content with 90%, output written materials to learners with 57%, whilst input aural material shows only 28% and output aural material shows 24%. The data also shows that 99% the source of the material come from the textbook itself and there is only 1% materials comes from learners. The data of nature content covered non-fiction with 94%, fiction with 6%, and grammar explanation with 20%, song with 4% and learner’s personal information/opinion with 11%. In sum, the content material in the three textbooks are recommended to use both by teacher and learner because they are in with SLA principles.